2020
DOI: 10.1002/ente.202000432
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Physical Properties of Imidazolium Chloride Ionic Liquids with Pyrrolidinium or Piperidinium Cation Addition and Their Application in Dual‐Ion Batteries

Abstract: Herein, nonflammable ionic liquid (IL) electrolytes are prepared for dual‐ion batteries (DIBs) by mixing 1‐methyl‐1‐propylpyrrolidinium chloride (P13Cl) or 1‐butyl‐1‐methylpiperidinium chloride (PP14Cl) with 1,2‐dimethyl‐3‐propylimidazolium chloride (DMPICl)/aluminum chloride (AlCl3) to form mixed IL electrolytes. Then, viscosity, ionic conductivity, thermal stability, and electrochemical limits measurements are recorded to reveal the fundamental properties of the mixed IL electrolytes for DIBs, which are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The calculated ECW of BMP-AlCl 4 (4.06 V) is little higher compared to that of BMP-OTf of (3.90 V). Our calculated ECW using AIMD-min of BMP-AlCl 4 is 4.06 V, which is comparable to that of the experimentally reported pyrrolidinium-based IL Pyr1,3-AlCl 4 (3.7 V) . The AIMD-min-calculated ECW value of DMPI-AlCl 4 is 3.48 V, which is higher compared to the calculated values of other imidazolium-based ILs, which is also in agreement with the previous report .…”
Section: Resultssupporting
confidence: 90%
“…The calculated ECW of BMP-AlCl 4 (4.06 V) is little higher compared to that of BMP-OTf of (3.90 V). Our calculated ECW using AIMD-min of BMP-AlCl 4 is 4.06 V, which is comparable to that of the experimentally reported pyrrolidinium-based IL Pyr1,3-AlCl 4 (3.7 V) . The AIMD-min-calculated ECW value of DMPI-AlCl 4 is 3.48 V, which is higher compared to the calculated values of other imidazolium-based ILs, which is also in agreement with the previous report .…”
Section: Resultssupporting
confidence: 90%
“…Cations and anions of the ILs can also be intercalated into the host materials, though limited study has been observed on this concept both experimentally and computationally [25,27,70–72] . In general, carbonaceous host materials such as graphite and polycyclic aromatic hydrocarbons (PAHs) are used as electrodes, which have enough space to accommodate the large size cations and anions of ILs [50] .…”
Section: Electrode Design For Dibsmentioning
confidence: 99%
“…Cations and anions of the ILs can also be intercalated into the host materials, though limited study has been observed on this concept both experimentally and computationally. [25,27,[70][71][72] In general, carbonaceous host materials such as graphite and polycyclic aromatic hydrocarbons (PAHs) are used as electrodes, which have enough space to accommodate the large size cations and anions of ILs. [50] We have conceptually demonstrated the dual graphite battery (DGB) with DMPI-AlCl 4 ionic liquid electrolyte, upon mixing of 1 : 1 ratio of 1,2-dimethyl-3propyl imidazolium chloride (DMPIÀ Cl) and AlCl 3 salt.…”
Section: Ionic Liquid Intercalating Electrodesmentioning
confidence: 99%
“…Ionic liquids (ILs) have played an important role in designing a new class of electrolytes due to them possessing certain interesting properties, such as a higher ionic conductivity, a low vapor pressure, and a broad electrochemical window, which are important in the development of the battery technology. The electrochemical reaction has mainly been focused on due to it possessing a high oxidative and reductive stability of the IL electrolyte, which results in a higher electrochemical stability window, thus accepting the high cut-off charging voltage (4.0–5.0 V). ,, Carlin et al have studied different metal-free IL-based cations, such as 2,3-dimethyl-1-propyl imidazolium (DMPI + ),1-ethyl-3-methyl imidazolium (EMI + ), and N -butyl- N -methyl pyrrolidinium (BMP + ) coupled with anions such as AlCl 4 – , CF 3 SO 3 – , PF 6 – , and BF 4 – as electrolytes in DIBs. , Our previous computational study has demonstrated DGB with a DMPI-AlCl 4 IL-based electrolyte, where the natural graphite-based battery shows a higher discharge voltage of 3.74 V, which is in good accordance with the experimental voltages . Owing to the large size of the organic DMPI cation, the interlayer distance of the graphite anode is expanded from 3.4 to 7.8 Å in the charging process.…”
Section: Introductionmentioning
confidence: 99%